Collisional and photoexcitation of transition metal clusters - Parry, I (2014)
The properties of transition metal clusters differ from those of both atomic and bulk size regimes. Such clusters are incompletely understood and potentially useful, making them attractive targets for further study. The very smallest clusters studied in this thesis (CuO, Cu2 and Cu3) have been investigated with velocity map imaging. 1+1' photodissociation of CuO X 2Π3/2 was observed, via the C, D, E, F and H states of CuO. CuO* was photodissociated to form Cu(2D3/2) + O(1D2). D0(CuO) was determined to be 3.041±0.030 cm-1. Non-resonant three-photon Cu2 photodissociation occurred throughout the energy range studied to produce one ground-state and one highly-excited copper atom,Cu*. Cu* was ionised by a single additional visible photon. Nearly all Cu* atoms with internal energies between 41000 and 53000 cm-1 were observed. D0(Cu2) has been calculated to be 1.992±0.037 eV. Features arising from photodissociation of Cu3 were observed in the Cu+ and Cu2+ ion yield spectra and images. Their structure was ill-resolved due to uncertainties in the internal energy of both parent Cu3 and product Cu2. These features correspond to single-photon dissociation of Cu3 to produce metastable D-states of the copper atom and vibrationally excited Cu2. One series of features implies a previously-unobserved state of either Cu2 or Cu3. RhnN2O+ and RhnON2O+ (n=5, 6) were collisionally activated in collision-induced dissociation (CID) experiments with Ar and 13CO. These experiments were carried out in a Fourier Transform Ion Cyclotron Resonance(FT-ICR)spectrometer. Argon collisions induced both N2O desorption and N2O reduction. The branching ratios observed reproduced those seen in prior IR-MPD experiments. 13CO was observed to chemisorb to the cluster upon collision, activating not only N2O desorption and reduction but also CO oxidation. Formation of CO2 was noted to be particularly rapid on the n=5 cluster compared to the n=6 cluster. Reactions of RhnN2O+ (n=4-6) clusters were also activated by black body radiation. This technique is known as BIRD - black-body induced infrared radiative dissociation. These studies revealed that the N2O desorption barrier exceeds the N2O reduction barrier on all clusters studied, but that the entropic favourability of desorption increases its rate relative to reduction with increasing cluster internal energy. The BIRD rate was much reduced upon cooling the ICR cell to 100 K. A further test of the BIRD mechanism increased the number of N2O ligands and hence the absorption rate. An approximately linear increase in the dissociation rate of Rhn(N2O)m+ was observed with index m. Deviations from linearity were caused by variations in the N2O desorption rate. In the case of Rh5(N2O)m+, desorption rates corresponded closely to N2O binding energies calculated by density functional theory. The system was modelled using a master equation approach.